Jaundice on Presentation Is Associated with Higher In-Patient Mortality and Complications in Patients Admitted for Acute Pancreatitis: A Retrospective Study Based on National Inpatient Sample Database - Nishit Patel; Krishna Bodrya; Kirten Patel; Nishi Patel; Dhruvanshu Patel; Ronak Modi; Ayaz Matin (Gastroenterology Research and Practice)
Pancreatitis usually presents with characteristic abdominal pain, radiological findings, and elevated lipase. The presence of jaundice may hint at a biliary etiology; however, it is not always present. We hypothesized that the presence of jaundice is associated with worse outcomes in patients admitted with pancreatitis. We conducted a retrospective analysis using the National Inpatient Sample, inquiring about patients admitted with pancreatitis with and without jaundice between October 2015 and December 2017. The primary outcome was in-hospital mortality in patients admitted for pancreatitis with and without jaundice. Secondary outcomes were the median length of stay, hospitalization cost, the incidence of ventilator-dependent respiratory failure (VDRF), acute respiratory distress syndrome (ARDS), sepsis, septic shock, dehydration and electrolyte disturbances, and ascites. A total of 1,267,744 patients were admitted with pancreatitis from October 2015 to December 2017. Among them, 8855 (0.7%) had concomitant jaundice on presentation. In-hospital mortality in this group was 4.3%. The patients with pancreatitis and jaundice had higher odds of in-hospital mortality (adjusted odds ratio [aOR]: 1.51, 99% CI 1.35–1.68, p<0.0001) as compared to those without jaundice. Patients with jaundice showed a significantly higher incidence of sepsis (15.2% vs. 9.6%, p<0.0001), septic shock (4.1% vs. 2.9%, p<0.0001), ascites (6.5% vs. 3.1%, p<0.0001), and dehydration and electrolyte disorders (47.6% vs. 43.8%, p<0.0001). Patients with jaundice also had higher total hospital costs ($11,412 vs. $7893, p<0.0001). There was no statistical difference in ARDS, VDRF, and median length of stay. In conclusion, patients admitted for pancreatitis with jaundice had worse outcomes, including in-hospital mortality and complications, compared to those without jaundice.